Analisis Proses Rekrutmen dan Seleksi Karyawan pada PT. Wijaya Kusumo Joyo Mulyo - Nafisatul Ilim; M. Isa Anshori (BADAN PENERBIT STIEPARI PRESS, 2025)
This study aims to analyze the recruitment and selection process at PT. Wijaya Kusumo Joyo Mulyo, an outsourcing service company. A qualitative approach was used, involving observation, interviews, and documentation. The results show that the recruitment process consists of several stages: receiving job requests, job posting, administrative selection, interviews, psychological tests, and onboarding. However, challenges arise such as difficulty in finding qualified candidates, ineffective job postings, and candidates resigning shortly after hiring due to mismatched expectations. Solutions implemented include stricter screening, targeted job advertisements, and presenting real work conditions through video during interviews. This research is expected to contribute to improving recruitment effectiveness in outsourcing companies.